School District Leadership Matters - Sheppard, Bruce. author. aut Link
X, 144 p.
Keywords: School District Leadership Matters challenges policy makers, administrators, and academics in the field of educational leadership to reassess their traditional approaches to learning, working, and planning. The authors believe that government restructuring, standards-based reforms, and centrally imposed strategic planning have been painfully ineffective. As a consequence, student learning has become increasingly superficial and inauthentic. This book bridges the traditional divide between the generalizations of social science theory on the one hand and the world of educational practice on the other. It argues that a more promising approach to education reform is through effective school district leadership. Sheppard, Brown and Dibbon draw on their collective experience both as educational leaders and researchers of leadership, having spent five years researching and working in one school district. Here, they show how a district superintendent can successfully navigate the paradoxes and challenges of facilitating collaborative leadership in a school district with a traditionally hierarchical organizational structure. As a conclusion to their work, the authors highlight what they call five ‘recognitions’ that deepen readers’ understanding of school district leadership. They illuminate, too, ways that senior level practitioners can apply theory to practice in order to break down the traditional hierarchical bureaucracies that inhibit learning, and create professional learning communities. School District Leadership Matters urges researchers, graduate students, practitioners, and policymakers to focus on improving authentic learning for all students and argues that the best hope rests with effective school district leadership. This empirically-based yet practical book provides new insights and questions for academic researchers and will inspire policy makers and practitioners to imagine what could be and towork towards it.